2007
DOI: 10.1542/peds.2007-0476
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Singular Excessive Computer Game and Television Exposure on Sleep Patterns and Memory Performance of School-aged Children

Abstract: The results suggest that television and computer game exposure affect children's sleep and deteriorate verbal cognitive performance, which supports the hypothesis of the negative influence of media consumption on children's sleep, learning, and memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
229
4
13

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(266 citation statements)
references
References 37 publications
11
229
4
13
Order By: Relevance
“…29 The association between television viewing and computer use and sleep duration is supported by several other studies. 13,16 They might impair sleep quality and duration, for example, by increasing the arousal state, 30 or alternatively, sleeping less might lead to more leisure time to fill in with television viewing and computer use.…”
Section: Discussionmentioning
confidence: 99%
“…29 The association between television viewing and computer use and sleep duration is supported by several other studies. 13,16 They might impair sleep quality and duration, for example, by increasing the arousal state, 30 or alternatively, sleeping less might lead to more leisure time to fill in with television viewing and computer use.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome dichotomized the sleep scale at 0 to 1 (59% at baseline) versus 2 to 10 (41%), so that children were defined as having "any sleep problem" if the parent answered that at least 1 sleep problem occurred 5 to 7 days per week, or at least 2 sleep problems occurred 2 to 4 days per week. The sleep measures were collected at baseline and each follow-up time point (6,12, and 18 months after beginning the intervention).…”
Section: Discussionmentioning
confidence: 99%
“…Although this finding has been consistently replicated with high levels of use, bedtime use, and violent or frightening media content, [1][2][3][4][5][6][7] effects have been observed across cultures and in all media formats (television, 6,[8][9][10] video games, [10][11][12] and computers 11,13,14 ) and across the age spectrum, including preschoolers, 2,7-9 school-aged children, 1,[3][4][5][6] and adolescents and adults. [13][14][15] Much of the existing research linking media use to child sleep problems has been crosssectional, however, raising the possibility that the causality is reversed; that is, that sleep problems are leading to increased media use, evening media use, and exposure to violent media content, rather than the other way around.…”
mentioning
confidence: 97%
“…The use of computers before bedtime has also been shown to have the same effect, and this finding has been demonstrated in a wide range of countries and cultures. 45,46,[48][49][50][51] Engaging in a greater number and range of sleep-interfering activities before going to bed has also been associated with less nocturnal sleep and more daytime sleepiness in adolescents. 45 Several mechanisms have been postulated about how media disrupts sleep.…”
Section: Electronic Media and Sleepmentioning
confidence: 99%
“…40 One study found that subjective sleepiness was lower, sleep latency was longer, and rapid eye movement (REM) sleep was shorter in subjects after playing video shooting games, independent of the brightness of the screen used. 56 Another study that compared playing an interactive computer game with watching a movie on television in the evening 51 found a decline in verbal memory performance, prolonged sleep latency, and an increase in light sleep in the computer game cohort.…”
Section: Electronic Media and Sleepmentioning
confidence: 99%